Indonesia Between Asean Countries and the World in Hydroelectricity - Darmawi . (IAES Indonesia Section, 2014)
Hydropower is predicted to be the most favourable energy regarding the global needs to cope with the global warming and the low cost energy resources utilization. Fossil fuel tends to depletion in the coming decades and the fossil energy price will race up. The states which energy is depend only on oil will result in the fragile economic base. Hydropoelectricity is now being energy developed even in a leading petroleum producer country. Indonesia with 75.000 MW hydroelectricity potential all over the country is hoped to generate more power in hydro energy to ascend the percentage of the state renewable energy consumption as a part of Indonesia process to diversify the domestic energy consumption to keep the economic away from oil dependency. Hydropower is the largest source of renewable energy of the world. In year 2005, some 2950 TWh of hydropower was generated, equivalent to 90% of electricity from world renewable energy consumption.